Studi Bias pada Kelompok Masyarakat Rumah Tangga Di Jawa Barat - Laely Purnamasari, - (2021)
Studi ini bertujuan untuk menganalisis bagaimana pengaruh overconfidence bias, representativeness bias, availability bias, confirmation bias, hindsight bias, illusion of control bias, loss aversion bias, endowment bias, self-control bias, regret aversion bias, status quo bias terhadap keputusan keuangan pada masyarakat Jawa Barat. Selain itu tujuan penelitian ini untuk mengetahui bagaimana pengaruh overconfidence bias, representativeness bias, availability bias, confirmation bias, hindsight bias, illusion of control bias, loss aversion bias, endowment bias, self-control bias, regret aversion bias, status quo bias terhadap keputusan keuangan. Bagaimana pola bias prilaku di Indonesia dalam mempengaruhi keuangan keputusan masyarakat kemudian dibandingkan dengan pola di negara emerging market maupun dengan negara non emerging market. Dalam penelitian ini bias prilaku merupakan variabel utama yang terdiri dari bias kognitif dan bias emosional. Bias kognitif terdiri dari sub variabel yaitu overconfidence bias, representativeness bias, availability bias, confirmation bias, hindsight bias, illusion of control bias, sedangkan untuk bias emosional terdiri dari sub variabel loss aversion bias, endowment bias, self-control bias, regret aversion bias, status quo bias. Populasi dalam penelitian ini yaitu masyarakat Jawa Barat yang berada di sektor pekerjaan pertanian, kehutanan, dan perikananan, real estat, dan penyedia akomodasi, makan dan minum yang berada di Jawa Barat. Adapun populasi dalam penelitian ini mencakup 9 kota yang ada di Jawa Barat. Teknik sampling yang digunakan dalam penelitian ini proportional random sampling. Sampel dalam penelitian ini sebanyak 768 responden yang tersebar di Jawa Barat dan pembagian sampel didasarkan pada populasi per kota yang ada di kota Bogor, Sukabumi, Bandung, Cirebon, Bekasi, Depok, Cimahi, Tasikmalaya dan kota Banjar. Metode penelitian yang digunakan deskriptif verifikatif. Teknik analisis menggunakan regresi multifel. Hasil penelitian menunjukkan bahwa Overconfidence bias, confirmation bias, Hindsight bias, self control bias, memiliki pengaruh negatif terhadap keputusan keuangan masyarakat Jawa Barat. Representative bias, Availability bias, Illusion of control bias, Endowment bias, Regret aversion bias memiliki pengaruh positif, terhadap pembuatan keputusan keuangan masyarakat Jawa Barat. Loss aversion bias dan Status quo bias tidak memiliki pengaruh terhadap keputusan keuangan masyarakat Jawa Barat. Kelompok rumah tangga memoderasi pengaruh representativenes bias, availability bias, hindsight bias, illusion of control bias, loss aversion boas, regret aversion bias terhadap keputusan keuangan masyarakat rumah tangga di Jawa Barat. Kelompok rumah tangga tidak memoderasi pengaruh overconfidence bias, confirmation bias, endowment bias, self control bias dan status quo bias terhadap pembuatan keputusan keuangan. Kata Kunci: Bias Prilaku, Bias Kognitif, Bias Emosional, Keputusan Keuangan. ABSTRACT BIAS STUDY ON HOUSEHOLD COMMUNITY GROUP IN WEST JAVA This study aims to analyze how the effect of overconfidence bias, representativeness bias, availability bias, confirmation bias, hindsight bias, illusion of control bias, loss aversion bias, endowment bias, self-control bias, regret aversion bias, status quo bias on financial decisions in West Java community. In addition, the purpose of this study is to find out how the effect of overconfidence bias, representativeness bias, availability bias, confirmation bias, hindsight bias, illusion of control bias, loss aversion bias, endowment bias, self-control bias, regret aversion bias, status quo bias towards decisions finance. How is the pattern of behavioral bias in Indonesia in influencing public financial decisions and then compared with patterns in emerging market countries and non-emerging market countries. In this study, behavioral bias is the main variable consisting of cognitive bias and emotional bias. Cognitive bias consists of sub-variables namely overconfidence bias, representativeness bias, availability bias, confirmation bias, hindsight bias, illusion of control bias, while for emotional bias consists of sub-variables loss aversion bias, endowment bias, self-control bias, regret aversion bias, the status quo is biased. The population in this study is the people of West Java who are in the agricultural, forestry, and fisheries sectors, real estate, and providers of accommodation, food and drink in West Java. The population in this study includes 9 cities in West Java. The sampling technique used in this study is proportional random sampling. The sample in this study was 768 respondents spread across West Java and the distribution of the sample was based on the population per city in the cities of Bogor, Sukabumi, Bandung, Cirebon, Bekasi, Depok, Cimahi, Tasikmalaya and Banjar cities. The research method used is descriptive verification. The analysis technique uses multiple regression. The results showed that the Overconfidence bias, confirmation bias, Hindsight bias, self-control bias, had a negative influence on the financial decisions of the people of West Java. Representative bias, Availability bias, Illusion of control bias, Endowment bias, Regret aversion bias have a positive influence on the financial decision making of the people of West Java. Loss aversion bias and status quo bias have no influence on the financial decisions of the people of West Java. The household group moderates the influence of representativeness bias, availability bias, hindsight bias, illusion of control bias, loss aversion boas, regret aversion bias on the financial decisions of households in West Java. The household group did not moderate the effect of overconfidence bias, confirmation bias, endowment bias,self control bias and status quo bias on financial decision making. Keywords: Behavioral Bias, Cognitive Bias, Emotional Bias, Financial Decisions.